2011
DOI: 10.1097/sle.0b013e318220f1c7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes of Laparoscopic Wedge Resection for Gastrointestinal Stromal Tumors of the Stomach of Less Than 5 cm in Diameter

Abstract: Laparoscopic wedge resection of GISTs of <5 cm in diameter is a safe and oncologically feasible technique offering good long-term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…[3][4][5][6] The technique is, however, more controversial for gastric adenocarcinoma. A large body of evidence comes from the Asian literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5][6] The technique is, however, more controversial for gastric adenocarcinoma. A large body of evidence comes from the Asian literature.…”
Section: Discussionmentioning
confidence: 99%
“…The first laparoscopic gastric resection was reported in 1993. 2 Since then, minimally invasive gastric surgery has gained general acceptance for benign conditions [3][4][5] and some malignant ones for which extended resection or lymphadenectomy is not required. 3,6 Its role in the treatment of gastric adenocarcinoma is still debated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…No clear evidence of level III or higher defines the type of GIST for which laparoscopic local gastrectomy is recommended. A retrospective study demonstrated that laparoscopic local gastrectomy can be safely performed if the tumor size is no greater than 5 cm in diameter . Another retrospective study that categorized patients according to tumor size, with a 2 cm diameter being the cut‐off, showed that although extended surgical time and hospitalization were observed in the group of patients with tumors larger than 2 cm, laparoscopic local gastrectomy could be performed safely in both groups, with no postoperative recurrence or metastasis .…”
Section: Clinical Question 3: Is Laparoscopic Local Gastrectomy (K654mentioning
confidence: 99%
“…(7,8) In the meantime, laparoscopic resection with a negative gross margin is oncologically justified for gastric GISTs smaller than 5 cm. (9-13) However, it still remains unknown whether minimally invasive resection of small intestinal GIST is technically and oncologically feasible. To the best of our knowledge, there have been no study evaluating both the technical safety and oncologic feasibility of laparoscopic resection of performed for GISTs of small intestine.…”
Section: Introductionmentioning
confidence: 99%